2015
DOI: 10.3109/00365521.2015.1047792
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of inflammatory bowel disease in Iceland 1995 – 2009. A nationwide population-based study

Abstract: This study shows statistically significant increase in the incidence of UC during the study period. The incidence of CD has however remained stable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 17 publications
2
8
0
2
Order By: Relevance
“…Similar to the increased prevalence over time, we observed a continuous increase in the incidence of UC. This finding is consistent with some recent Scandinavian studies, all restricted to analyses of incidence only . Sjöberg et al observed a mean annual incidence of 20.0 per 100 000 inhabitants in the Uppsala region, Sweden, between 2005 and 2009, which is comparable to the rate of 18.1 per 100 000 during the last 5‐year period in our study .…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Similar to the increased prevalence over time, we observed a continuous increase in the incidence of UC. This finding is consistent with some recent Scandinavian studies, all restricted to analyses of incidence only . Sjöberg et al observed a mean annual incidence of 20.0 per 100 000 inhabitants in the Uppsala region, Sweden, between 2005 and 2009, which is comparable to the rate of 18.1 per 100 000 during the last 5‐year period in our study .…”
Section: Discussionsupporting
confidence: 94%
“…Assessment of temporal trends of UC is mostly based on the extrapolation of studies with short observation periods . Historically, an increasing incidence of UC was initially reported from North America and northern parts of Europe, including several regions in Sweden . Studies on the incidence of UC in the primary catchment area of Örebro University Hospital, Örebro, Sweden, have reported an increasing incidence rate from 2.7 per 100 000 inhabitants in 1939‐1958 to 3.3 in 1963 to 14.9 per 100 000 inhabitants in 1987 .…”
Section: Introductionmentioning
confidence: 99%
“…Our findings confirm that the incidence of IBD continues to increase in Denmark. This finding is in accordance with recent observations in other high‐incidence areas such as France, Spain, Canada and our neighbouring Scandinavian countries, as well as in previous low‐incidence areas of Eastern Europe and Asia …”
Section: Discussionsupporting
confidence: 93%
“…The frequency of IBD-U is usually reported to be higher among pediatric patients compared to that of the adult population: 13 versus 6% in a meta-analysis [6], and to be decreasing over disease course [7]. In well characterized IBD cohorts, the proportion of IBD-U has been reported to range from 1 to 20% in adults [8][9][10][11][12][13][14][15][16][17][18][19][20] and from 4 to 22% in pediatric patients [21][22][23][24][25][26][27][28][29][30][31][32][33]) (Table 1).…”
Section: Introductionmentioning
confidence: 99%